Diagnosis and treatment of hind limb muscle strain injuries in 22 dogs - Nielsen, C.; Pluhar, G. E. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
The anamnesis was obtained from the medical records of 22 dogs diagnosed with hind limb muscle strain injury over a four-year period. The signalment, history, diagnostic imaging and clinical findings, treatment and outcome are described. The affected dogs were primarily from large breeds. Although only a few clients reported a specific injury, 11 dogs were admitted for an acute onset of lameness of unknown origin. The hip adductor muscles were affected in 21 dogs, and 11 dogs had previously undergone orthopaedic surgery of the affected limb. The dogs were primarily diagnosed by physical examination, although the diagnosis was confirmed with ultrasound imaging in the two most recent cases. Neither concurrent orthopaedic nor neurological disease was found during the study period in four of 22 dogs, and another three dogs had only mild radiographic coxofemoral osteoarthritis that did not cause any clinical signs during the study period. All of the dogs were treated medically with some combination of rest, physical therapy, methocarbamol, and a non-steroidal anti-inflammatory drug (NSAID). The injury-associated lameness improved, or completely resolved, with conservative, non-surgical therapy in most dogs. Of the 15 dogs available for follow-up (mean 577 days), eight had complete resolution of their clinical signs, two showed significant improvement, and one showed some improvement. Muscle strain injury may be an under-diagnosed cause or contributor to acute hind limb lameness in large breed dogs, either alone or following orthopaedic surgery.
Keywords: Muscle strain injury; hip adductor muscles; canine